The Impact of Social Stigma on women’s recidivism: field study in Sharjah Correctional Prison Inmates - Alnaqbi, Eman; Alomosh, Ahmad (Al-Adab Journal, 2025)
The study aimed at identifying the effects of social stigma factors on women’s recidivism to crime in the Emirate of Sharjah. The study used the descriptive-analytical approach, and a sample of women who had returned to crime in Sharjah was selected. A questionnaire was applied to them. The results showed that the impact of both economic and social stigma factors on women’s return to crime was at a moderate level, with no statistically significant differences between their average responses to economic and social stigma factors. This indicates that these factors have an equal impact on women’s recidivism to crime in Sharjah. The research recommends integrating women into community jobs and providing support for poor families.